Comparison of conventional and advanced radiotherapy techniques for left-sided breast cancer after breast conserving surgery - Xie, Yibo (Med Dosim, 2020)
Whole breast radiotherapy (WBRT) after breast conserving surgery is the standard treatment to prevent recurrence and metastasis of early stage breast cancer. This study aims to compare seven WBRT techniques including conventional tangential, field-in-field (FIF), hybrid intensity-modulated radiotherapy (IMRT), IMRT, standard volumetric modulated arc therapy (STD-VMAT), non-coplanar VMAT (NC-VMAT) and multiple arc VMAT (MA-VMAT). Fifteen patients who were previously diagnosed with left-sided early stage breast cancer and treated in our clinic were selected for this study. WBRT plans were created for these patients and were evaluated based on target coverage and normal tissue toxicities. All techniques produced clinically acceptable WBRT plans. STD-VMAT delivered the lowest mean dose (1.1 ± 0.3 Gy) and the lowest maximum dose (7.3 ± 4.9 Gy) to contralateral breast, and the second lowest LAR (4.1 ± 1.4%) of secondary contralateral breast cancer. MA-VMAT delivered the lowest mean dose to lungs (4.9 ± 0.9 Gy) and heart (5.5 ± 1.2 Gy), exhibited the lowest LAR (1.7 ± 0.3%) of secondary lung cancer, NTCP (1.2 ± 0.2%) of pneumonitis, RCE (10.3 ± 2.7%), and LAR (3.9 ± 1.3%) of secondary contralateral breast cancer. NC-VMAT plans provided the most conformal target coverage, the lowest maximum lung dose (46.2 ± 4.1 Gy) and heart dose (41.1 ± 5.4 Gy), and the second lowest LAR (1.8 ± 0.4%) of secondary lung cancer and RCE (10.5 ± 2.8%). MA-VMAT and NC-VMAT could be the preferred techniques for early stage breast cancer patients after breast conserving surgery.